Pengaruh Persepsi, Mutu Pelayanan dan Fasilitas Terhadap Kepuasan Pasien Klinik Pratama PKU Muhammadiyah Tambak - Septi Nur Wahyudi , Khusnia (EKONOMI DAN BISNIS DIGITAL, 2024)
This study aims to determine the effect of perception, service quality and facilities on patient satisfaction at the Pratama PKU Muhammadiyah Tambak clinic. The sample in this study was 100 respondents taken using incidental sampling techniques. The analysis technique used in this study is a descriptive analysis technique, statistics including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis accompanied by partial tests (t-test) and simultaneous tests (f-test). The calculation process uses SPSS 27. Based on the analysis conducted, this study has succeeded in proving that perception, service quality and facilities on patient satisfaction at the Pratama PKU Muhammadiyah Tambak clinic, facilities have a significant effect on patient satisfaction at the Pratama PKU Muhammadiyah Tambak clinic.